Rearticulating home absent voices - Navarro, Louie T. (2014)
As the concept of home/home-place/home ownership is redefined by the accelerated growth of condominium living in Metro Manila - primarily bolstered by Overseas Filipino Workers' remittances - this article attempts to decipher the changing landscape of the city built from the hopes and dreams of an absent generation. By engaging Derrida's concept of difference in exploring the absence this phenomena engenders, an attempt will be made to reconstruct a space the identity of which is at a constant flux, in which meaning is forever deferred. and from the spatial character of 'home' as a residence, a retirement address or as an investment opportunity to the abstract notions of performance, aspirational and eventual suspended 'neither-here-nor-there' nature of the same embodied in cyberspace as home-place, one will see that, perhaps, homelessness, is but a small price to pay in home
ownership.
Keywords: Deconstructionism